Short Communication: The Effect of Organic and Aqueous Extracts of Salvia Fruticosa on Intestinal Motility - Suleiman Al-Khalil; Saadeh Suleiman; Abdul-Salam Abdul Ghani; Riyad Amin (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The effect of organic (methanol and ether) extracts, and aqueous (neutral). Acidic and basic) extracts from the leaves of Salvia fruticosa, on the spontaneous contractile activity of the rabbit ileum was studied. Both Organic extracts were found to inhibit the spontaneous activity of the rabbit ileum, and inhibit acetylcholine — induced contractions. On the other hand aqueous extracts did not show any effect. The effects of a series of organic solvent extracts on the ileum were studied.